HUKUM POLIGAMI DALAM PERSPEKTIF ULAMA FIQH - Aris Baidhowi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2012)
The fiqh ulama agree that the legal permissibility of polygamy in marriage is based on the word of Allah SWT, Surah of al-Nisa 'verse 3, which confirms that the polygamist husband conditions shall be fair to his wives. They recognize the value of justice in polygamy is something that is impossible to be realized. Therefore, the illat of legal permissibility of polygamy in Islam marriage is: that it shall not be encouraged by the motivation of biological sex and pleasure, but only by social and human motivation, since the interpretation of